Marcadores microssatélites ligados a locus de resistência ao oídio e ao padrão externo de frutos de melancia - Gama, Renata Natália Cândido de Souza (2015)
The powdery mildew is one of the most important foliar diseases that attack the watermelon and other cucurbits in Brazil and in the world. The principal identification elements by the consumer are based on the external appearance and quality of the fruit. The objective of this study was to identify microsatellite markers linked to resistance to powdery mildew and to the stripe pattern of watermelon fruits with microsatellite markers. Plants of the parents, F1 and F2, which are the result of a cross between the cultuvars BRS Opara (powdery mildew resistant and with clearly defined stripes fruit) and Pérola (powdery mildew susceptible and with diffuse stripes fruit), were phenotyped in the field for resistance or susceptibility to powdery mildew and, after of the harvest, the fruits was morphologically characterized. For these characteristics, 116 microsatellite markers were analyzed and the linkage analysis done in JoinMap 2.0. Segregation in the F2 population demonstrated that resistance powdery mildew and the stripe pattern are controlled by a single dominant gene. The microsatellite loci MCPI_11, CYSTSIN and BVWS02441 showed linked to the powdery mildew resistance gene at 2.6 cM with LODs ‘score’ of 31.42 and are located in chromosome two of the watermelon genome. The microsatellite loci MCPI_05 and MCPI_16 showed a linkage to the stripe patterns of watermelon fruits at a distance of 1.5 and 1.8 cM with a LODs ‘scores’ of 39.28 and 38.11 respectively, and are located in the chromosome six of the watermelon genome. These markers can be used in the marker assisted selection process in watermelon improvement programs.